2016
DOI: 10.1007/s00264-016-3317-x
|View full text |Cite
|
Sign up to set email alerts
|

Reamed intramedullary exchange nailing in the operative treatment of aseptic tibial shaft nonunion

Abstract: Purpose The aim of this study was to evaluate a standardized treatment protocol regarding the rate of secondary bone union, complications, and functional outcome. Methods This study was started as a prospective study in a single Level I Trauma Centre between 2003 and 2012. The study group consisted of 188 patients with the diagnosis of an aseptic tibial shaft nonunion. Exchange nailing was performed following a standardized surgical protocol. Long-term followup was analyzed for rate of bone healing and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…The authors suggested that owing to the high union rates with exchange nailing, it can be recommended as the first line of treatment for all kinds of aseptic tibial diaphyseal nonunions. Another prospective study consisting of 188 patients demonstrated osseous healing through a single exchange nail in 182 out of 188 aseptic tibial diaphyseal nonunions [30]. A systematic review of seven randomized control trials by Lam et al suggested that reamed intramedullary nailing is superior to nonreamed intramedullary nailing, as reamed nailing had a superior union rate with reduced chances of postoperative infection [31].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The authors suggested that owing to the high union rates with exchange nailing, it can be recommended as the first line of treatment for all kinds of aseptic tibial diaphyseal nonunions. Another prospective study consisting of 188 patients demonstrated osseous healing through a single exchange nail in 182 out of 188 aseptic tibial diaphyseal nonunions [30]. A systematic review of seven randomized control trials by Lam et al suggested that reamed intramedullary nailing is superior to nonreamed intramedullary nailing, as reamed nailing had a superior union rate with reduced chances of postoperative infection [31].…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Adequate fixation provides biomechanically stable construct, eliminates disturbing forces, and promotes healing. [ 19 , 20 ] Blocking screws may be necessary to correct the deformity or enhance the mechanical stability. Osteotomy shape, site, technique, grafting of the nonunion site, appropriate nail length and thickness, reaming amount, correction degree, and lengthening should be calculated preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, nonunion was the most prevalent complication of tibial shaft fractures due to insufficient soft tissue cover and high incidence of open fractures independent of the surgical fixation methods such as IMN, locking compression plating, or external fixation. [ 20 ] Intramedullary nailing provides more mechanical stability, enhances biological environment by autografting due to reaming, and supplies dynamic compression in the nonunion site.…”
Section: Discussionmentioning
confidence: 99%
“…Interlocking intramedullary nails have been widely used in acute humeral fractures, pathologic fractures and nonunions of the tibia or femur shaft, as for humerus xation, they have the advantages over plates of fewer tissue traumas, fewer circulatory impairments and lower risk of radial nerve injury [3]. Nailing or exchange nailing for humeral shaft nonunion had been successfully reported by some authors, the concept of this technology is improving nonunion segments biomechanical stability by using of a nail being at least one millimeter thicker than its diameter and fostering healing environment by transporting mesenchymal stem cells into the nonunion sites during reaming procedure [2,21]. However, the heal rates varied differently.…”
Section: Discussionmentioning
confidence: 99%